Deterministic transition of enterotypes shapes the infant gut microbiome at an early age - Xiao, Liwen; Wang, Jinfeng; Zheng, Jiayong; Li, Xiaoqing; Zhao, Fangqing (Genome Biology, 2021)
The succession of the gut microbiota during the first few years plays a vital role in human development. We elucidate the characteristics and alternations of the infant gut microbiota to better understand the correlation between infant health and microbiota maturation. We collect 13,776 fecal samples or datasets from 1956 infants between 1 and 3 years of age, based on multi-population cohorts covering 17 countries. The characteristics of the gut microbiota are analyzed based on enterotype and an ecological model. Clinical information (n = 2287) is integrated to understand outcomes of different developmental patterns. Infants whose gut microbiota are dominated by Firmicutes and Bifidobacterium exhibit typical characteristics of early developmental stages, such as unstable community structure and low microbiome maturation, while those driven by Bacteroides and Prevotella are characterized by higher diversity and stronger connections in the gut microbial community. We further reveal a geography-related pattern in global populations. Through ecological modeling and functional analysis, we demonstrate that the transition of the gut microbiota from infants towards adults follows a deterministic pattern; as infants grow up, the dominance of Firmicutes and Bifidobacterium is replaced by that of Bacteroides and Prevotella, along with shifts in specific metabolic pathways. By leveraging the extremely large datasets and enterotype-based microbiome analysis, we decipher the colonization and transition of the gut microbiota in infants from a new perspective. We further introduce an ecological model to estimate the tendency of enterotype transitions, and demonstrated that the transition of infant gut microbiota was deterministic and predictable.